2013
DOI: 10.4304/tpls.3.1.51-60
|View full text |Cite
|
Sign up to set email alerts
|

A Corpus-based Approach toward Teaching Collocation of Synonyms

Abstract: the aim of the study is to provide insights into the use of the corpus-based approach in L2 classes. The study aimed at comparing the effects of the corpus-based approach with the effects of the traditional approach on learning collocations of near-synonymous pairs. The study was run on 2 groups of L2 learners. One group named experimental group studied with concordancing and the other group named the control group studied with the traditional approach. The participants in each group were similar in terms of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 20 publications
3
25
0
Order By: Relevance
“…Jafarpour et al found that their corpus-based teaching approach had a significant effect on the students' knowledge and competence of collocations in the experimental group. According to Jafarpour et al (2013), student in both groups achieved a considerable progress; however, students in the experimental group showed a significant improvement in their writing proficiency after using the corpus producing more authentic language.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Jafarpour et al found that their corpus-based teaching approach had a significant effect on the students' knowledge and competence of collocations in the experimental group. According to Jafarpour et al (2013), student in both groups achieved a considerable progress; however, students in the experimental group showed a significant improvement in their writing proficiency after using the corpus producing more authentic language.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Jafarpour et al (2013) compared the effect of a corpus-based teaching of collocations applied on an experimental group to that of traditional approach applied on a control group. The researchers focused on teaching collocations of nearsynonymous pairs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The pilot study at the first stage included a collocation-recognition-targeted test, par tially modelled after Jafarpour et al (2013), McCarthy and O'Dell (2005), McKinlay and Hastings (2007), Nguyen and Webb (2016), and Smith (2005), and a posttest interview. The purpose of this stage was to identify the patterns and strategies participants used to select "oddsounding" word combina tions and build a hypothesis about potential factors that might have influ enced this recognition.…”
Section: Methodsmentioning
confidence: 99%
“…They argue that connections between words in collocations are dependent on a particular language (e.g., plastic surgery in English and пластическая операция [plastic operation] in Russian), and therefore are more difficult for language learners to recognize. Jafarpour, Hashemian, and Alipour (2013) and Webb and Kagimoto (2011) focus on synonyms for collo cates and nodes that might be similar or different in L1 and L2, which again impedes with collocation comprehension. Additionally, Peters (2016) identi fies that although congruent collocations are less likely to be problematic for recognition/recall in comparison to incongruent formulaic units, both are still a source of challenge for learners.…”
Section: Interlinguistic Factorsmentioning
confidence: 99%
See 1 more Smart Citation